Adaptive Spiritual Management in Qur’anic Education: Balancing Memorization Discipline and Child Readiness - Zainal Abidin; Ahmad Qusairi (Managere: Indonesian Journal of Educational Management, 2025)
This study examines the implementation of the Pra-PTPT Qiroati Program as a model of Qur’anic education management that seeks to balance memorization targets with children’s learning readiness and emotional development. The research responds to ongoing challenges faced by non-formal Qur’anic education institutions in maintaining structured learning discipline while adapting to the developmental needs of young learners. A qualitative case study approach was employed to explore institutional policy, instructional practices, and parental involvement within the program. Data were gathered through in-depth interviews, participatory engagement in learning activities, and examination of institutional learning records, and were analyzed using the interactive model of Miles and Huberman. The findings indicate that program effectiveness is shaped not only by the structured Qiroati method but also by teachers’ ability to adjust instructional strategies according to students’ engagement and learning conditions. The extended learning duration contributed to the formation of the study discipline; however, its sustainability depended on adaptive teaching practices that supported students’ emotional well-being. Parental involvement further reinforced learning continuity beyond instructional sessions, strengthening students’ motivation and consistency in memorization practice. The study highlights that flexible and collaborative management practices enable Qur’anic learning to remain structured while responsive to learners’ developmental needs. findings imply discussions in Islamic education management by emphasizing the integration of institutional regulation, adaptive pedagogy, and social support as interconnected elements that sustain effective Qur’anic education practice.